From Tradition to Modern Parenting: An Ethnography of Child Rearing Practices in a Sundanese Village - Illona Syahla Pramudita; Erna Herawati (ETNOSIA : Jurnal Etnografi Indonesia, 2026)
Child rearing practices among young mothers and young fathers in Sundanese semi-rural areas are changing rapidly, shaped by social transformation, digital media, and modern medical knowledge. While most studies focus on parenting as a way to preserve cultural values, this article examines how young mothers and young fathers are adapting their practices amid semi-urban change and what happens to local values such as pamali, extended family roles, and the use of the Sundanese language in everyday family life.Using ethnographic approach, this study was conducted in Cileles Village, West Java Province. Data was collected through participant observation and in-depth interviews with five mothers and three fathers who have children under five years old.The results show that child rearing practices have become an arena for cultural selection and rationalization. Young mothers and young fathers tend to adopt child rearing practices informed by digital knowledge and information, which are considered more relevant to children's growth and development needs. Sundanese cultural values such as silih asah, silih asih, and silih asuh are still recognized symbolically, but have undergone changes in form and in the intensity of their application. Shifts are evident in child stimulation practices, sleep arrangements, language use within the family, and less involvement of the extended family in child rearing. Rather than openly rejecting tradition, young mothers and young fathers engage in gradual and selective adaptations that subtly reconfigure child rearing as a medium of cultural inheritance. This study demonstrates that the transformation of Sundanese culture occurs not only in public or institutional domains but also within the domestic sphere. In the context of semi-urbanization, everyday parenting practices become an early locus of cultural change with long-term implications for cultural sustainability.